Plasticity of altruistic behavior in children - Lozada, Mariana (2014)
The present study investigates the plasticity of altruistic behavior in children, analyzing the effect of a short intervention on 6- to 7-year-olds. After a 10-session intervention performed in a school context, altruism significantly increased. The intervention, which included relaxation practices, cooperative activities and emotional security priming, positively modulated altruistic behavior in children, beyond reciprocation and reputation. The experiences of collaborating, feeling emotional security and attaining moments of relaxation increased participants’ awareness of themselves and of others, favoring the emergence of intrinsic altruism. These results are in line with our hypothesis that altruism is an embodied human resource, highly susceptible to experience within social contexts.